Trends, Effects, and Cooperation Interactions in Educational Contexts: Investigating the Interdisciplinary Landscape of Spirituality Research - Noor- Anidaisma, Noor- Anidaisma; Amat, Salleh; Awang, Mohd Mahzan; Ahmad, Mazita (Business Management and Strategy, 2023)
This study summarises the profound insights from the bibliometric analysis of educational spirituality research. The study examines spiritual research from 2005 to 2023 to understand its complex dynamics and patterns. This research quantifies and reveals trends to illuminate the multifaceted growth of spirituality across disciplines and the collaborative efforts, influential authors, and publishing entities that have advanced it. This study uses bibliometric analysis to provide a nuanced view of the field’s current state, its relationships with related concepts, and future directions. The study highlights the rise in spirituality research, especially in education, during COVID-19. This trajectory shows the field’s evolution and relevance to modern challenges. Citations show the research’s scholarly impact in distinct patterns of acknowledgment. Visualizing complex co-authorship networks with VOSviewer software reveals collaborative dynamics and diverse research directions. Spirituality research is interdisciplinary, as evidenced by its publication in various journals and publishers. This research engages 116 nations, demonstrating its global and interconnected nature. Citation analysis shows scholarly recognition across the study’s findings. The collaborative nature of academic research is reflected in Web of Science data’s panoramic view of research institutions’ contributions. Additionally, citation analysis reveals seminal references that have shaped spirituality research discourse. The Web of Science framework’s subject categories show spirituality research’s adaptability and interdisciplinary nature. The study concludes with a deep understanding of the research landscape, defined by an intricate interplay of clusters that vividly depict spirituality research’s reach across diverse human dimensions. These clusters demonstrate spirituality’s impact on personal development, environmental awareness, emotional well-being, healthcare, and more, weaving a tapestry of spirituality research’s importance across fields.